HIV-related Discriminatory Attitudes of Healthcare Workers in Bangladesh - Hossain, Mohammad Bellal; Kippax, Susan (Journal of Health, Population and Nutrition, 2010)
This study aimed at identifying the level of HIV-related discriminatory attitudes and related factors in a purposively- selected sample of healthcare workers (HCWs) in Bangladesh. In total, 526 HCWs from a number of hospitals and healthcare centres were interviewed using a structured questionnaire. A moderate level of discriminatory attitudes was observed. The factors associated with a high level of such attitudes among the HCWs were: high level of irrational fear about HIV and AIDS; working in teaching hospital rather than in non-teaching hospital and diagnostic centres; low level of education; and being male. The results indicate that programmes to reduce irrational fear about transmission of HIV are urgently needed. Key words: Acquired immunodeficiency syndrome; Cross-sectional studies; Discrimination; Healthcare workers; Human immunodeficiency virus; Stigma; Bangladesh DOI: 10.3329/jhpn.v28i2.4892 J Health Popul Nutr 2010 Apr; 28(2): 199-207